Fungal Endophytes in Plants - Gary A. Strobel (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Dear Colleagues, This Special Issue is dedicated to fungi that are found as endophytes in the world's plants. Among many other things, it covers newly-discovered fungi that are endophytic. The role of the endophyte in the plant microbiome is of emerging interest, and aspects of are included. Secondary products of endophytes are receiving renewed attention as some have been found that are potential fuels, antibiotics, antioxidants, and anticancer agents, as well as immunosuppressive compounds. Aspects concerning the physiological/biochemical/role of the endophyte, as it relates to its host are also of interest. It goes without saying that this volume also includes aspects of the genetics and epigenetics of endophytes, especially as they relate to the host genome or the production of valuable and important products. Dr. Gary A. Strobel Guest Editor